Relationship of cytokine gene polymorphism and the development of liver fibrosis in patients with chronic hepatitis B&C - Usychenko, K.; Berdnyk, Y. (Journal of Education, Health and Sport, 2023)
One of the features of the spread of infectious diseases is an increase in the number of mixed infections caused by various types of microorganisms: bacteria, viruses, protozoa, fungi, mycoplasmas, chlamydia, etc. In mixed infections, the simultaneous presence of several pathogens leads to not only to the complex interaction of pathological processes, but also complicates the diagnosis and choice of treatment. Mixed hepatitis is characterized by high biochemical activity and histological changes, the presence of signs of portal hypertension. Infection with two viruses increases the risk of developing hepatocellular carcinoma. It should be noted that in patients with HBV infection, the development of hepatocellular carcinoma is possible at the stage of chronic hepatitis before the onset of liver cirrhosis. The aim of the study: to investigate a comprehensive assessment of the allelic polymorphism of the IL-4 (rs2243250), IL-10 (rs1800896), TNFα (rs1800620), SMAD family member 7 (rs4939827) and eIF3h (rs16892766) genes with the degree of fibrosis in patients with chronic hepatitis B&C. Materials and methods. In the course of the study, 62 patients with chronic hepatitis B&C were examined before the start of treatment and after the end of the course of antiviral therapy. The degree of liver fibrosis was established by FibroScan. Molecular genetic studies included the determination of polymorphic variants of the IL-4 (rs2243250), IL10 (rs1800896), TNFα (rs1800620), SMAD family member 7 (rs4939827), eIF3h (rs16892766) genes. Polymorphism was studied by amplification of the corresponding regions of the genome by PCR. Results and discussions. Genotypes CC IL-4 (rs2243250), GG IL-10 (rs1800896), GG TNFα (rs1800620), AA SMAD family member 7 (rs4939827), TT eIF3h (rs16892766) have a protective effect on the course of chronic hepatitis B&C, as they are established in patients with chronic hepatitis B&C with a lower degree of fibrosis. Heterozygous CT IL-4 (rs2243250), GA IL-10 (rs1800896), GA TNFα (rs1800620), CC SMAD family member 7 (rs4939827), CC eIF3h (rs16892766) have a profibrotic effect on the course of chronic hepatitis B&C, therefore that they are established in patients with chronic hepatitis B&C with a greater degree of fibrosis.In patients with a low stage of fibrosis, the genotypes CC IL-4 (rs2243250), GG IL-10 (rs1800896), GG TNFα (rs1800620), AA SMAD family member 7 (rs4939827), TT eIF3h (rs16892766), are most often determined. In patients with a degree of fibrosis, other genotypes were detected, namely CT IL-4 (rs2243250), GA IL-10 (rs1800896), GA TNFα (rs1800620), CC SMAD family member 7 (rs4939827), CC eIF3h (rs16892766). Сonclusions. The revealed differences in the frequency of occurrence of various gene polymorphisms in healthy subjects and patients with chronic hepatitis indicate a certain predisposition to the development of a chronic inflammatory process in the liver.